Effect of membrane character and solution chemistry on microfiltration performance - Gray, S.; Ritchie, C.; Tran, Truyen; Bolto, B.; Greenwood, Paul; Busetti, Francesco; Allpike, Bradley (Elsevier Science, 2008)
To help understand and predict the role of natural organic matter (NOM) in the fouling oflow-pressure membranes, experiments were carried out with an apparatus that incorporates automatic backwashing and long filtration runs. Three hollow fibre membranes of varying character were included in the study, and the filtration of two different surface waters was compared. The hydrophilic membrane had greater flux recovery after backwashing than the hydrophobic membranes, but the efficiency of backwashing decreased at extended filtration times. NOM concentration of these waters (7.9 and 9.1 mg/L) had little effect on the flux of the membranes at extended filtration times, as backwashing of the membrane restored the flux to similar values regardless of the NOM concentration. The solution pH also had little effect at extended filtration times. The backwashing efficiency of the hydrophilic membrane was dramatically different for the two waters, and the presence of colloid NOM alone could not explain these differences. It isproposed that colloidal NOM forms a filter cake on the surface of the membranes and that small molecular weight organics that have an adsorption peak at 220 nm but not 254 nm were responsible for "gluing" the colloids to the membrane surface. Alum coagulation improved membrane performance in all instances, and this was suggested to be because coagulation reduced the concentration of "glue" that holds the organic colloids to the membrane surface.